2014
DOI: 10.1007/s10067-014-2727-7
|View full text |Cite
|
Sign up to set email alerts
|

The COL5A1 gene is associated with increased risk of carpal tunnel syndrome

Abstract: The direct causes of idiopathic carpal tunnel syndrome (CTS), a common upper limb entrapment neuropathy, remain unknown. It is however generally accepted that an increase in pressure within the carpal tunnel structure, which contains nine flexor tendons, causes compression of the median nerve. The involvement of these tendons in the aetiology of CTS cannot be excluded. Variants within the collagen, type V, alpha 1 (COL5A1) gene, which encodes for the α1 chain of type V collagen, an important regulator of fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The Bst UI RFLP (rs12722) is a common C to T single nucleotide polymorphism (SNP) within the COL5A1 3′ untranslated region which may alter COL5A1 messenger RNA (mRNA) stability ( Laguette et al, 2011 ). Previous studies identified the Bst UI restriction fragment length polymorphism (RFLP) to be associated with chronic Achilles tendinopathy ( Mokone et al, 2006 ; September et al, 2009 ), anterior cruciate ligament ruptures ( O’Connell et al, 2015 ; Posthumus et al, 2009 ; Petr et al, 2014 ), carpal tunnel syndrome ( Burger et al, 2015 ) and properties of the knee ligament ( Kubo et al, 2013 ). In addition, this SNP was also associated with joint flexibility ( Brown et al, 2011 ), joint range of motion (ROM) ( Collins et al, 2009 ) and endurance running performance ( Brown et al, 2011 ; Collins and Posthumus, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Bst UI RFLP (rs12722) is a common C to T single nucleotide polymorphism (SNP) within the COL5A1 3′ untranslated region which may alter COL5A1 messenger RNA (mRNA) stability ( Laguette et al, 2011 ). Previous studies identified the Bst UI restriction fragment length polymorphism (RFLP) to be associated with chronic Achilles tendinopathy ( Mokone et al, 2006 ; September et al, 2009 ), anterior cruciate ligament ruptures ( O’Connell et al, 2015 ; Posthumus et al, 2009 ; Petr et al, 2014 ), carpal tunnel syndrome ( Burger et al, 2015 ) and properties of the knee ligament ( Kubo et al, 2013 ). In addition, this SNP was also associated with joint flexibility ( Brown et al, 2011 ), joint range of motion (ROM) ( Collins et al, 2009 ) and endurance running performance ( Brown et al, 2011 ; Collins and Posthumus, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few nonsyndromic CTS pedigrees with autosomal-dominant inheritance have been reported, but no causal genes or loci were identified 16,17,[20][21][22][23][24][25] . Variants in some genes, including BGN, ACAN, COL5A1, and IL6R, have been associated with the risk of sporadic CTS [26][27][28] . Since environmental factors, such as repetitive hand use, contribute to CTS by preferentially affecting the dominant hand, the high percentage of bilateral CTS (about 60%) 29,30 and twin studies (estimated 46% heritability) 31 suggests that genetic factors significantly influence CTS susceptibility.…”
mentioning
confidence: 99%
“…These variants define two major functional forms of the 3′-UTR, which we have previously termed the C-allelic and T-allelic forms (figure 2B) 42 46. Although not all five of the variants have been genotyped in the studies, considering all the published investigations to date, the C-allelic form appears nevertheless to be under-represented in chronic Achilles tendinopathy,27 42 lateral epicondylitis13 and carpal tunnel syndrome 19. The associated 3′-UTR region does not exactly overlap between all these injuries19 and could reflect the complexity of the biological role the COL5A1 3′-UTR could play in the tissue-specific regulation of type V collagen production.…”
Section: Genetic Risk Factors For Musculoskeletal Soft Tissue Injuriementioning
confidence: 99%
“…As reviewed above, versions of the T-allelic form are associated with several musculoskeletal soft tissue injuries (table 1). 13 19 27 31 42…”
Section: Functional Significance Of Genetic Risk Factors For Musculosmentioning
confidence: 99%